PENINGKATAN KINERJA UMKM MELALUI KEPRIBADIAN DAN STRATEGI PEMASARAN DIMODERASI OLEH PENGGUNAAN TEKNOLOGI INFORMASI DITENGAH BADAI COVID-19 - Albar, Elyas; Munaing, Munaing; Aswar, Aswar (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2023)
The aim of the study is to determine the contribution of personality and marketing strategies in improving THE performance of MSMEs, both directly and moderated by the Use of Information Technology. Quantifiative research method of an exploitatory approach where the variables of Personality, Marketing Strategy, Technology Use and MSME Performance. The population is MSMEs in Makassar, a sample of respondents of 100 MSME actors in the city of Makassar and a random sampling technique. Data collection by disseminating questionnaires, observations and documentation. Research questionnaire with Liker Scale tested for validity and reability.Â Hypothesis testing was carried out using the Sem-PLS (partial least square) analysis technique. The results of this study show that the personality and marketing strategy variables have a positive and significant effect on the performance of MSME actors. Personality and Marketing Strategy have a positive and significant effect on the performance of MSMEs moderated by the use of Information Technology